2015
DOI: 10.4103/0975-7406.163479
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe sleep apnea secondary to juvenile arthritis with temporomandibular joint replacement and mandibular advancement

Abstract: Variations affecting the growth centers can severely affect the normal formation and subsequent function of vital musculoskeletal structures. We report a case of bilateral condylar atrophy with a history of juvenile arthritis (JA) resulting in progressive obstructive sleep apnea (OSA) in adulthood. In addition to this, the case report emphasizes the role of temporomandibular joint replacement and advancement of the mandible to correct progressive OSA secondary to idiopathic JA. Computed tomography revealed mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With regards to treatment of OSA with concomitant TMJ disease, reports of mandibular advancement with simultaneous bilateral TMJ replacement have been reported successfully (22). In this case, computed tomography (CT) showed that the condylar hypoplasia, resultant micrognathia, and decreased retrolingual and retropharyngeal airway space were all significantly improved with the surgical procedures.…”
Section: The Relationship Between Osa and Tmj Diseasementioning
confidence: 84%
“…With regards to treatment of OSA with concomitant TMJ disease, reports of mandibular advancement with simultaneous bilateral TMJ replacement have been reported successfully (22). In this case, computed tomography (CT) showed that the condylar hypoplasia, resultant micrognathia, and decreased retrolingual and retropharyngeal airway space were all significantly improved with the surgical procedures.…”
Section: The Relationship Between Osa and Tmj Diseasementioning
confidence: 84%
“…63 Of 5 case series of TJR that included patients with JIA, all reported positive outcomes. [64][65][66][67][68] It must be noted, however, that the long-term stability of autologous and alloplastic constructs has never been directly compared.…”
Section: E29mentioning
confidence: 99%
“…The temporomandibular joint (TMJ) is one of the most commonly involved joints in children with juvenile idiopathic arthritis (JIA), and may lead to impaired joint function, pain, growth impairment with dentofacial deformities [ 1 – 4 ], a reduced posterior airway space with related comorbidities [ 5 , 6 ], and impaired quality of life [ 7 ]. The rate of TMJ arthritis varies significantly (40–90%) in different JIA-cohorts using magnetic resonance imaging (MRI) [ 8 – 10 ], as reviewed by Larheim et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%